Marine and terrestrial endophytic fungi: a mine of bioactive xanthone compounds, recent progress, limitations, and novel applications. (3rd April 2022) - Khattab, Amira R.; Farag, Mohamed A.
Abstract: Endophytic fungi are a kind of fungi that colonizes living plant tissues presenting a myriad of microbial adaptations that have been developed in such a hidden environment. Owing to its large diversity and particular habituation, they present a golden mine for research in the field of drug discovery. Endophytic fungal communities possess unique biocatalytic machinery that furnishes a myriad of complex natural product scaffolds. Xanthone compounds are examples of endophytic secondary metabolic products with pronounced biological activity to include: antioxidant, antimicrobial, anti-inflammatory, antithrombotic, antiulcer, choleretic, diuretic, and monoamine oxidase inhibiting activity. The current review compiles the recent progress made on the microbiological production of xanthones using fungal endophytes obtained from both marine and terrestrial origins, with comparisons being made among both natural resources. The biosynthesis of xanthones in endophytic fungi is outlined along with its decoding enzymes. Biotransformation reactions reported to be carried out using different endophytic microbial models are also outlined for xanthones structural modification purposes and the production of novel molecules. A promising application of novel computational tools is presented as a future direction for the goal of optimizing microbial xanthones production to include establishing metabolic pathway databases and the in silico analysis of microbial interactions. Metagenomics methods and related bioinformatics platforms are highlighted as unexplored tools for the biodiversity analysis of endophytic microbial communities that are difficult to be cultured.